THE INFLUENCE OF CORPORATE GOVERNANCE ON TAX AVOIDANCE (STUDY ON BASIC INDUSTRY AND CHEMICALS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE) - Saprudin Saprudin; Revan Andhitiyara; Ribkha Putri Dameria (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research aims to determine the influence of corporate governance consisting of managerial ownership, board of commissioners structure, audit committee and audit quality, on tax avoidance on basic industry and chemicals companies listed on the Indonesia Stock Exchange in 2017-2019. The variables studied were managerial ownership, board structure, audit committee and audit quality. The type of research used is causative, which uses population data from 78 companies listed on the Indonesia Stock Exchange. The sampling method used in this study was purposive sampling and obtained 13 companies that passed the criteria. The results showed that managerial ownership and audit quality had a significant impact on tax avoidance, while the structure of the board of commissioners and audit committee had no significant effect on tax avoidance. The implementation of corporate governance has a significant effect in tax avoidance activities.